The Neverlands of Nature: Exploring Representations of the Non-Human in Visitor Information Publication Material on Swedish National Parks - Fälton, Emelie; Hedrén, Johan (Journal of Northern Studies, 2021)
In this paper, we distinguish, make visible, and problematize how the non-human world (often depicted as nature) in Swedish national parks comes into being through representations in visitor information publications, and what the productive effects of those representations are. Through a discursive analysis, we identify seven discursive formations that concern portrayals of the non-human world. On the one hand, it is represented as extraordinary and sublime pieces of wild and pristine nature—and on the other, as ordinary and accessible. Despite this divergence, these kinds of spaces function as national heritage with an elitist status, which creates hierarchizations between national parks and other spaces, but also between the national parks themselves. North and south are assigned different attraction values and portrayed as desirable in different contexts. The north is wild, pristine, and sublime, while the south is safe, available, and always open to tourists. Furthermore, the material generates portrayals of national parks as places for learning, where the non-human world is displayed, explored, experienced, and taught. The uniting force of these formations is the focus of national parks as places of otherness, which turns them into heterotopian neverlands far away from the mainland of modernity.